The Mapping Person Job-Fiton Human Resource Management: Bibliometric Analysis on Scopus Database - Purwanitasari, Lili; Sopiah, Sopiah; Zagladi, Arief Noviarakhman (Universitas Negeri Surabaya, 2025)
In the changing working world, the perception of Person-Job Fit (fit between an individual and a job) plays a crucial role in improving employee performance and satisfaction. This fit involves an individual's abilities, competency/knowledge, interests as well as values with the demands, responsibilities, and work environment, which is the main focus of various studies related to person-job fit. This study aims to mapping out and provide a bibliometric overview of the topic of person-job fit, to identifying research trends by uncovering popular topics, identifying the relationship between concepts such as job satisfaction, organization commitment, and job performance, demonstrating commonly used approaches of methodology such as equation structural modelling, mapping the network authors, institutions, and countries that can build collaboration, and helping researchers quickly and systematically find relevant literature and lastly the result support the strategic development of Human Resource theory and practices. The research data was taken from articles published in the Scopus database between 2019 and 2024, and 63 articles were found using the VOSviewer application. The results showed that the most articles on person-job fit were published in 2022 (15 articles), with the journal “International Journal of Human Resource Management” as the most frequently published. The most affiliations came from the National Institute of Development Administration with 2 documents, while China was the country with the most publications. The topic is mainly covered in the area of business, management, and accounting. Keywords often associated with person-job fit include:Person-Organization Fit, Job Satisfaction, Turnover Intention, Person-Environment Fit, Job Performance, Organizational Commitment, Work Environment, Work Engagement, Job Involvement, and Structural Equation Modelling.